Evaluating organizational level IT innovation adoption factors among global firms - Omar Ali; Peter A. Murray; Shahnawaz Muhammed; Yogesh K. Dwivedi; Shqipe Rashiti (Journal of Innovation & Knowledge (JIK), 2022)
This study explores a range of organizational factors that drive success in organizational level information technology (IT) innovation adoption. A comprehensive model of organizational level IT innovation adoption is presented based on a context-mechanism-outcome perspective and by drawing on relevant theories. The proposed model is empirically tested using data from 1988 company executives across a wide range of organizations globally. A research model and the related hypotheses are tested using structural equation modelling. The study found that organizational level IT innovation readiness conceptualized through technology readiness and internal expertise is a key mediator for successful organizational level technology adoption. Other organizational factors such as top management support, organizational structure, and organization culture, were positively related to the overall level of IT innovation readiness and organizational level technology adoption. Considering that there are many organizational factors that influence the adoption of technology, future research should extend the research framework and include additional variables that could support IT innovation adoption outcomes. The study makes a significant contribution to the existing literature by providing empirical evidence related to the organizational factors necessary for a successful IT innovation adoption at an organizational level.
Keywords: 650; Structural equation modelling; IT innovation readiness; Organizational factors; Organizational information technology adoption